PENGEMBANGAN DESA WISATA MELALUI RITUAL DESA NOGOSARI KECAMATAN PACET KABUPATEN MOJOKERTO - Mokhammad Ibnu Kawakib (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2025)
This research discusses the cultural diversity and traditions in Indonesia, with a focus on the Kirim Dawuhan tradition in Nogosari Village, Pacet Subdistrict. This tradition is an expression of gratitude by the villagers for the abundant water sources in their village and plays a significant role in environmental preservation and strengthening social bonds within the community. This study aims to address how the development of a Village Tourism through Rituals in Nogosari Village can be achieved and to provide practical and academic contributions to village development and further policies. The research method employed is a qualitative descriptive approach involving four youths from Nogosari Village as informants. The results reveal that the Kirim Dawuhan tradition encompasses the "Ubo Rampe" component, which holds profound meanings and life values. Nogosari Village possesses natural and cultural potentials that can serve as a foundation for Village Tourism development. This development could involve creating tourism packages based on the Kirim Dawuhan tradition, training for tour guides, collaboration with relevant parties, and utilizing technology and social media for promotion. In summary, the development of Village Tourism through the Kirim Dawuhan tradition in Nogosari Village has substantial potential for enhancing the community's economy, preserving culture, and maintaining environmental sustainability. Collaboration between local communities, the government, and related stakeholders is pivotal in achieving these goals. With the right and sustainable approach, this village has the opportunity to become an engaging and meaningful tourist destination, while maintaining a balance between cultural preservation, environmental conservation, and sustainable economic development.